A primer on rules of origin as non-tariff barriers - Dzmitry Kniahin; Jaime De Melo (Journal of Risk and Financial Management, 2022)
An explosion of different preferential rules of origin (PROO) has accompanied the spread of preferential trade agreements (PTAs) around the world. Complying with PROO requirements entail costs for producers, exporters, and customs officials. Observers, firms, customs officials, and policymakers have advocated simplification as well as harmonization. The paper surveys the literature drawing on the extensive database in ITC's Rules of Origin Facilitator (ROF) database covering 54,000 distinct PROO spread across 370 PTAs to illustrate the issues covered in the literature. We review what we know about the compliance costs associated with PROO requirements. We illustrate these costs graphically and summarize through mathematical decomposition of compliance costs along two dimensions: distortionary costs resulting from the restrictiveness of PROOs and administrative costs. We survey the existing evidence in literature by themes: (i) determinants of the utilisation of preferences; (ii) effects on third countries outside the PTA; (iii) choice of rule; (iv) preference margin and complexity of rules; (v) trade deflection; and (vi) firm-level evidence. In conclusion, drawing lessons from the empirical literature is a complicated exercise because preference uptake, an important indicator of compliance costs, is only available for a handful of PTAs at the disaggregated product level.
Keywords: 650; AfCFTA; compliance costs; product-specific rules of origin; regime-wide rules of origin; rules of origin